Enhanced wear resistance of engineered glass-ceramic by nanostructured self-lubrication. (15th April 2019) - Fuertes, V.; Cabrera, M.J.; Seores, J.; Muñoz, D.; Fernández, J.F.; Enríquez, E.
Abstract: A new kind of micro-nanostructured glass-ceramic based on albite and anorthite crystallizations, >90%, has been obtained following a fast sintering processing route. Flexural strength values up to 111 MPa and microhardness values of 9.5 GPa are measured, supposing an improvement of 60% regarding current glazes for ceramic floor tiles for high transit areas. The hierarchical micro-nanostructuration of these glass-ceramics favour crack deflection, which implies a reduction of brittleness in these materials and a consequent increase of fracture toughness of 40% regarding a standard glass-ceramic. Tribological properties are also evaluated, showing a decrease in the friction coefficient (μ) of 36% and a surprising reduction of the wear rate (WR ) larger than one magnitude order, in both micro-nanostructured glass-ceramics, concerning a standard one. Worn tracks analysed by Multi-Mode Optical Profilometry and FE-SEM measurements revealed that nanocrystals present in the microstructure work as solid lubricants, favouring body sliding over their surface and noticeably reducing μ, WR and the surface damage suffered. Wear mechanism undergone by both glass-ceramics is unlike other glass-ceramics, similar to a polishing process, without any apparent material spalling. All of these findings make the micro-nanostructured materials very promising candidates to be used in high-performance self-lubricating applications. Graphical abstract: Unlabelled Image Highlights: Novel micro-nanostructured glass-ceramics obtained by a fast sintering processing route. Hierarchical micro-nanostructure extremely improves mechanical properties. Wear mechanism undergone is unlike other glass-ceramics, like a polishing process. Nanocrystals work as solid lubricants, reducing surface damage suffered. Very promising candidates to be used in high-performance self-lubricating applications.